Effect of exercise program before learning activities to improve gross motor skills of students - Muhammad Luthfi Muslim; Irwan Hermawan; Z. Arifin; Alam Hadi Kosasih; Azhar Ramadhana Sonjaya (Program Studies of Physical Education, Faculty of Teacher Training and Education, Musamus University, 2024)
Physical education is crucial for the whole growth of students, thereby addressing cognitive, motor, social, and emotional dimensions. However, studies conducted on fourth grade children at Suci State Elementary School revealed that certain pupils exhibited suboptimal gross motor abilities, which can be attributed to less engaging instructional approaches. This study suggests implementing a conventional game-based sports program prior to learning activities as a means to enhance students' gross motor skills. There is an expectation that this method will enhance students' motivation and engagement in an enjoyable learning experience, therefore facilitating the optimal development of their motor skills. Objectives. Evaluate the impact of pre-learning sports programs on enhancing pupils' gross motor abilities. Materials and Methods. The employed methodology is the Experiment with Preexperimental Design, specifically the One Group Pretest-Posttest Design type. The study sample consisted of 14 individuals selected using the purposive sampling technique. Using Locomotor Basic Movements, the study instrument assesses 12 competencies, which include: During the initial 6 skills, I prompt the child to transition between different locations using various methods. Furthermore, throughout the final 6 talents, the youngster will demonstrate their proficiency in ball control through several means. The acquired data underwent systematic analysis in multiple phases, encompassing normality tests, homogeneity tests, and hypothesis testing. Results. Based on the data analysis conducted using the t-Test: Paired two samples for means, it is evident that the obtained significance is 0.000. Since the significance is less than 0.05, the null hypothesis (H0) is rejected in favor of the alternative hypothesis (H1). Therefore, it can be concluded that implementing a sports program before learning activities can enhance students' gross motor skills. Conclusions. Implementing fitness initiatives prior to educational activities might enhance pupils' gross motor skills.